: Sun tracking solar power system - Deyar Idhilie; Israa Sabri (My University, 2022)
The purpose of this project is to implement the most efficient control algorithm of dual-axis sun tracker. The simulation gives the tracker angles that position the solar panel along the sun’s rays such that maximum solar irradiation is absorbed by the panel. The traditional solar panels used in homes and factories ,etc… are fixed with a certain angel, sun-tracking system allow the solar panel to adjust its position according to the position of sun in the sky. A dual-axis sun trackers have 2 degree of freedom, it could rotate both vertically and horizontally, thus they can track sun’s entire motion in the sky from east to west and from south to north. LDRs are used to position the sun location in the sky and motors are used to change the panel position/angle on both axis. As the work of the project included hardware design and implementation, it needs software programming for the micro-controller unit of the solar tracker. The system utilized an Arduino to control motion of the servo motors. The amount of rotation was determined by the Arduino, based on inputs retrieved from the sensors. The generated power from the solar panel will feed a smart home model (electrical fan, LED, smoke alarm) with energy. Before that the DC wave generated by the solar panel would have been change to another DC wave form which will be suitable to be stored at the batteries connected to the system using DC battery charger. The home system will be supplied with the necessary energy and any excess energy will remain stored in the battery. An auto-cleaner is added to the panel to clean it from the built dust in order to make sure that the efficiency of the panel is not effected. The main advantage of this approach that it gives the solar panel a high degree of flexibility, which allows higher energy output.